2019
DOI: 10.1002/1873-3468.13504
|View full text |Cite
|
Sign up to set email alerts
|

Senescence caused by inactivation of the homeodomain transcription factor Pdx1 in adult pancreatic acinar cells in mice

Abstract: In this study, we used tamoxifen‐inducible Elastase‐Cre–mediated inactivation of pancreatic and duodenal homeobox1 (Pdx1), an indispensable gene during embryonic pancreatogenesis, to investigate the role of Pdx1 in adult pancreatic exocrine tissue. We found that Pdx1 depletion in approximately 50% of acinar cell mass did not show any macroscopic phenotype. Lineage tracing experiments revealed that the percentage of Pdx1‐depleted cells did not change initially but gradually decreased, while the proliferation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This may have caused a responsive miR-17-5p upregulation aimed at their negative regulation. A similar mechanism may be in place, albeit indirectly, for miR-16-5p and Pre-B-cell leukemia transcription factor 1 (PDX1), as PDX1 depletion is known to induce senescence [40] and impaired mitophagy [41]. Therefore, we suspect that the presence of active ATG5/7alt pathway elements in both control and knockout models caused a gradual pressure on the miR feedback circuitry, eventually tipping the balance toward miR upregulation, resulting in ATG5/7alt suppression, which in turn may have led to mitochondrial dysfunction and senescence.…”
Section: Discussionmentioning
confidence: 99%
“…This may have caused a responsive miR-17-5p upregulation aimed at their negative regulation. A similar mechanism may be in place, albeit indirectly, for miR-16-5p and Pre-B-cell leukemia transcription factor 1 (PDX1), as PDX1 depletion is known to induce senescence [40] and impaired mitophagy [41]. Therefore, we suspect that the presence of active ATG5/7alt pathway elements in both control and knockout models caused a gradual pressure on the miR feedback circuitry, eventually tipping the balance toward miR upregulation, resulting in ATG5/7alt suppression, which in turn may have led to mitochondrial dysfunction and senescence.…”
Section: Discussionmentioning
confidence: 99%
“…PDX1 is also a key regulator of β-cell proliferation and differentiation. Loss of PDX1 led to mouse pancreatic agenesis 43 , while PDX1 deficiency in acinar was found to cause cell senescence 44 . Our results also showed that acute FAM3A repression and β cell-specific FAM3A gene knockout could impair pancreatic β-cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The exocrine pancreas is composed of acinar cells (>90%) which, under aging and stress, dedifferentiate and acquire an early pancreatic progenitor phenotype, concomitant with activation of the Ras-Mapk pathway and of a senescence program [ 90 ]. The dedifferentiated acinar cells were proliferation arrested by the acquisition of a senescent state, characterized by induction of p53, p21 Cip1 , p16 Ink4a , and SA-β-Gal [ 91 , 92 , 93 , 94 ].…”
Section: Cellular Senescence In β-Cells and Diabetesmentioning
confidence: 99%